2023
DOI: 10.1111/joor.13485
|View full text |Cite
|
Sign up to set email alerts
|

Step‐back anterior repositioning splint retraction for temporomandibular joint disc displacement with reduction in adult patients

Abstract: BackgroundAnterior repositioning splint (ARS) is used to treat temporomandibular joint (TMJ) disc displacement with reduction (DDwR). However, high recurrence rate remains a problem especially in patients with unstable occlusions.ObjectiveThis study optimised standard ARS therapy and proposed a step‐back ARS retraction (SAR) method in adult patients with DDwR.MethodsDental examinations and magnetic resonance imaging of TMJ were obtained before treatment (T0), 1 to 3 months (T1), 3 to 6 months (T2) and 6 to 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A strength of our study was that during the control appointments, there was no “walking back” of the condyles. There was no need for the step-back anterior repositioning splint retraction method [ 40 ], as, in our study, the ThP was calculated individually by the CMR method. Stabilizer adjustments were only made to maintain the final therapeutic position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strength of our study was that during the control appointments, there was no “walking back” of the condyles. There was no need for the step-back anterior repositioning splint retraction method [ 40 ], as, in our study, the ThP was calculated individually by the CMR method. Stabilizer adjustments were only made to maintain the final therapeutic position.…”
Section: Discussionmentioning
confidence: 99%
“…Once the disc is recaptured, then the disc–condyle complexes are subsequently ‘walked back’ along the posterior slope of the articular eminence by periodic modification, i.e., by grinding of the splint [ 37 , 38 , 39 ]. In a recent study, this walking back of the condyle was termed step-back anterior repositioning splint [ 40 ]. A long-term clinical trial with MRI evaluation demonstrated that mandibular repositioning can be effective in reducing disk displacement, particularly on anteriorly displaced disks.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Al-Saleh et al (2020) [ 19 ] and Li et al (2021) suggests that properly fitted splints can help reduce parafunctional habits, minimize joint loading, and provide pain relief. Different types of splints, such as stabilization splints and anterior repositioning splints, have shown promising results in various TMD subtypes [ 20 ].…”
Section: Introductionmentioning
confidence: 99%